Formalization of Technological Processes for Accounting and Storage of Information in a Healthcare Institution - Kovalenko, O.S.; Kozak, L.M.; Romanyuk, O.O.; Najifan Tumanjani, M.; Maresova, T.A. (Control systems & computers, 2020)
The purpose of the paper is to develop the formalized components of the digital medicine integrating environment to ensure effective interaction between patients, family physicians and health care workers at various levels. Results. The general structure of information flows of the integrative environment of digital medicine is described and the formalized representation of health care business processes are developed.An analysis of the characteristics of the main actors actively involved in medical care was provided, and the access level to medical information of each participant, which is an obligatory condition, in particular in the case of mobile medicine, was determined. To ensure the storage of this information, an infologicalmodel of the database was developed, indicating the internal links between the blocks of the database. Model elements are defined for each block: classes, attributes and operations (using UML). Метою роботи є розроблення формалізованих складників інтегрувального середовища цифрової медицини для забезпечувати ефективної взаємодії між пацієнтами, сімейними лікарями та працівниками закладів охорони здоров’я різного рівня. Результати. Описано загальну структуру інформаційних потоків інтегрувального середовища цифрової медицини та розроблено формалізоване подання бізнес-процесів закладу охорони здоров’я. Надано аналіз характеристик основних учасників (акторів) процесу надання медичної допомоги та визначено рівень доступу до медичної інформації кожного учасника,що є невід’ємною умовою, зокрема у разі застосування мобільної медицини. Для забезпечення зберігання цієї інформації розроблено інфологічну модель бази даних зазначенням внутрішніх зв’язків між блоками БД. Для кожного блоку визначено елементи моделі: класи, атрибути і операції (з використанням UML). С помощью разработанного модуля для мобильного устройства врачу предоставляется возможность определять эффективность определенного типа хирургического и терапевтического лечения для дальнейшей коррекции тактики лечения, а также автоматически сформулировать необходимые статистические отчеты о деятельности больницы, отделения или каждого врача.